Rancang Bangun Sistem Informasi Akademik Website Untuk Madrasah Diniyah Awaliyah Ubudiyah - Muhammad Junaedi; I Gede Putu Krisna Juliharta; Eka Grana Aristyana Dewi (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2023)
MDA Ubudiyah is an educational institution that focuses on Islamic religious studies. In this place the authors also conducted research. From the sistem currently used, the writer finds the fact that administrative activities there are still paper-based. This is a problem because of frequent data corruption and impractical data retrieval. Therefore the authors offer a solution by creating a website-based information sistem. The development method used in building this system is the Agile software development method. The data collection was carried out by interviewing the Ubudiyah MDA administrators and making observations. The programming language used is the Personal home page (PHP), then the database uses MySQL. The result of this research is the creation of a website-based information sistem to assist administrative activities at MDA Ubudiyah.